ANALYSIS OF FINANCIAL PERFORMANCE USING THE CAMEL METHOD AT PT. BANK SULSELBAR - Risa Pradista, Noviana; Darmawan Natsir, Uhud; Nurman, Nurman (Journal Management & Economics Review (JUMPER), 2023)
This study aims to determine the financial performance of PT Bank Sulselbar as measured using the CAMEL Method (Capital, Assets, Management, Earning, and Liquidity). The object of research is PT Bank Sulselbar. The type of research used is quantitative descriptive research, the type of data used is primary and secondary data, the sample used is the financial statements of PT Bank Sulselbar from 2017 to 2021. The results in this study are the financial health condition of PT. Bank Sulselbar in the 2017 and 2018 periods is in the